Copper and zinc fractionation in soils treated with CuO and ZnO nanoparticles: The effect of soil type and moisture content - Jośko, Izabela (The Science of the total environment, 2019)
Increased use of nano-products results in the release of nano-constituents into various environmental media, including soils. The metal components of inorganic nanoparticles are subject to partitioning during the various soil phases. The aim of the study presented here was to estimate Zn and Cu distribution in different soils after treatment with nano-ZnO and nano-CuO (10 mg kg−1) under various moisture conditions (30, 50 and 80% of water holding capacity). Samples were incubated for 24 h, 3 and 24 months. In addition, the effect of the form of Cu (nano-CuO, nano-Cu, bulk-CuO and CuCl2) on Cu partitioning was estimated. The assessment of metal distribution was made using sequential analysis, which allowed to distinguish five fractions: exchangeable (F1), carbonate (F2), bound with Fe-Mn oxides (F3), bound with organic matter (F4), and residual (F5). The results of the analyses revealed that in the treated and untreated soil the percentage of potentially bioavailable metal fractions (F1, F2) was considerably lower than the total content of fractions considered to be stable (F3, F4, F5). Fractionation of Cu and Zn differed, which could have resulted from different rates of solubility as well as from soil properties and moisture content. [Display omitted] •The Cu fractionation in soil was affected by particle size and form of Cu•The greatest increase of concentration of metals was observed in fraction bound with organic matter•Aging resulted in a drop of share of metal bound to NOM and an increase of the percentage of fraction bound to Fe/Mn oxides